Determinants of Work-Life Balance Dimensions on Satisfaction of Bread Employees in Malang - Riyan Hamidi; Fauzan Almanshur (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This study examines the impact of work-life balance, assessed through the dimensions of time balance, involvement, and satisfaction, on employee job satisfaction within the bakery sector in Malang City. The employed research method is a quantitative approach utilizing a descriptive framework. This research was performed on employees in the bread industry in Malang City with the saturation sample approach, yielding 100 responses. Primary data were acquired via surveys, whereas supplementary data were gathered through employee interviews. Data analysis encompasses the assessment of the measurement model (outer model), the structural model (inner model), and hypothesis testing with SPLS 4.0. The statistical test results indicated that time balance did not significantly correlate with employee job satisfaction, evidenced by a T-statistic of 1.157, below the T-table value of 1.96, and a P-value of 0.206, beyond the 0.05 threshold. The engagement variable significantly affects employee work satisfaction, as evidenced by a T-statistic of 2.702, surpassing the T-table value of 1.96, and a P-value of 0.007, below 0.05. The balance of satisfaction significantly influences employee job satisfaction, evidenced by a T-statistic of 8.042, surpassing the T-table value of 1.96, and a P-value of 0.000, below 0.05. The simultaneous combined effect of time balance, involvement, and satisfaction does not significantly influence employee work satisfaction. The T-statistic value of 1.265 is less than the T-table value of 1.96, and the P-value of 0.248 surpasses the 0.05 criterion. The findings demonstrate that work-life balance influences employee job satisfaction, mainly through the aspects of involvement and satisfaction within the baking sector in Malang City.